2022
DOI: 10.1186/s12883-022-02923-8
|View full text |Cite
|
Sign up to set email alerts
|

SOX-1 antibodies in a patient with Crohn’s disease: a case report

Abstract: Background The anti-SOX-1 antibodies have been mainly associated with Lambert-Eaton Myasthenic Syndrome (LETMS) and Small-Cell Lung Cancer (SCLC). In this report, we describe the interesting case of a patient with serum anti-SOX-1 antibodies and Crohn’s Disease (CD) with ensuing neurological symptoms. Case presentation A Caucasian 67-year-old female was admitted to the Emergency Department with seizures, vertigo, emesis, nausea, postural instabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Her IBD course is unusual and she also had orbital pseudotumor, a rare extra-intestinal manifestation of IBD [8]. A description of anti-SOX1 antibodies in a patient with CD and Lambert-Eaton myasthenic syndrome also points towards a far wider association of different types of neuromuscular involvement in patients with MG [50].…”
Section: Discussionmentioning
confidence: 99%
“…Her IBD course is unusual and she also had orbital pseudotumor, a rare extra-intestinal manifestation of IBD [8]. A description of anti-SOX1 antibodies in a patient with CD and Lambert-Eaton myasthenic syndrome also points towards a far wider association of different types of neuromuscular involvement in patients with MG [50].…”
Section: Discussionmentioning
confidence: 99%
“…studies that reported SOX1 antibodies in non-PNS, mainly neuropathies, as the detection of SOX1 antibodies was done by a single technique (immunoblot or ELISA) and the result was not confirmed by CBA (10)(11)(12)(13)(14)(15)(16).…”
Section: Figurementioning
confidence: 99%